Amyloids in Site-Specific Autoimmune Reactions and Inflammatory Responses - Huang, Yan-Mei; Hong, Xue-Zhi; Shen, Jian; Geng, Li-Jun; Pan, Yan-Hong; Ling, Wei; Zhao, Hai-Lu (Frontiers in Immunology, 2020)
Amyloid deposition is a histological hallmark of common human disorders including Alzheimer’s disease (AD) and type 2 diabetes. Although some reports highlight that amyloid fibrils might activate the innate immunity system via pattern recognition receptors, here we provide multiple lines of evidence for the protection by site-specific amyloid protein analogs and fibrils against autoimmune attacks: (1) strategies targeting clearance of the AD-related brain amyloid plaque induce high risk of deadly autoimmune destructions in subjects with cognitive dysfunction; (2) administration of amyloidogenic peptides with either full length or core hexapeptide structure consistently ameliorates signs of experimental autoimmune encephalomyelitis (EAE); (3) EAE is exacerbated following genetic deletion of amyloid precursor proteins; (4) absence of islet amyloid co-exists with T cell mediated insulitis in autoimmune diabetes and autoimmune polyendocrine syndrome; (5) use of islet amyloid polypeptide agonists rather than antagonists improves diabetes care; and (6) common suppressive signaling pathways by regulatory T cells are activated in both local and systemic amyloidosis. These findings indicate dual modulation activity mediated by amyloid protein monomers, oligomers, and fibrils to maintain immune homeostasis. The protection from autoimmune destruction by amyloid proteins offers a novel therapeutic approach to regenerative medicine for common degenerative diseases.